Development through Seasonal Worker Programs : The Case of New Zealand's RSE Program - Gibson, John; McKenzie, David (World Bank, Washington, DC, 2014)
Seasonal worker programs are increasingly seen as offering the potential to be part of international development policy. New Zealand's Recognised Seasonal Employer program is one of the first and most prominent of programs designed with this perspective. This paper provides a detailed examination of this policy through the first six seasons. This includes the important role of policy facilitation measures taken by governments and aid agencies. The evolution of the program in terms of worker numbers is discussed, along with new data on the (high) degree of circularity in worker movements, and new data on (very low) worker overstay rates. There appears to have been little displacement of New Zealand workers, and new data show Recognised Seasonal Employer workers to be more productive than local labor and that workers appear to gain productivity as they return for subsequent seasons. The program has also benefitted the migrants participating in the program, with increases in per capita incomes, expenditure, savings, and subjective well-being. Taken together, this evidence suggests that the program is largely living up to its promise of a "triple win" for migrants, their sending countries in the Pacific, and New Zealand.